Apakah Tanggung Jawab Sosial Mempengaruhi Earning Management? Literature Review - Rosmawati, Rida; Arief, Meta; Widyaningsih, Aristanti (Jurnal Pendidikan Akuntansi (JPAK), 2023)
The purpose of this study was to determine whether corporate social responsibility has an effect on earnings management. The research method used is a systematic literature review from various national and international journals. The results of this study indicate that there is a research gap among researchers regarding the relationship between corporate social responsibility and earnings management. Some researchers find that social responsibility has a significant negative effect on management earnings, which means that the better the company’s CSR activities, the smaller the earnings management practice, this is because the company will prioritize relationships with stakeholders and information disclosure. Meanwhile, some researchers found that CSR activities have no significant effect on earnings management. The cause of this difference is due to the differences in the countries studied, the measuring instruments used, and the ethical values ??in each company. This research is expected to provide an overview to further researchers in determining the appropriate object and measuring instrument tailored to the objectives of each research.